Diseño teórico de un biodigestor para la producción de biogás partiendo de la gallinaza producida en la finca “La Victoria” ubicada en la Vereda Los Ejidos en Vélez Santander (2021)
The present work carried out an alternative for the use of chicken manure produced in the La Victoria farm located in Vélez Santander, which corresponds to a theoretical design of a biodigester to produce biogas from this excreta. Different theoretical references were investigated that provide information on the physical-chemical characteristics of the ground manure, where the pH was averaged resulting in a data of 7.01, total solids of 93.12%, C / N ratio of 11, 79%, humidity of 30%, nutrients such as potassium of 1.89% and phosphorus of 4.27%; Based on this, the type of biodigester was selected using a Pugh matrix, relating and scoring aspects such as costs (30%), flow (25%), ease of construction (20%), biogas production (15%) and useful life (10%), obtaining the Chinese model as the most favorable biodigester with a score of 3.9.